THE INFLUENCE OF PROFITABILITY, LIQUIDITY, AND DIVIDEND POLICY TOWARDS FIRM VALUE OF CONSUMER GOODS COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Andoko Andoko; Cynthia Cynthia (Universitas Pelita Harapan, 2022)
This research aims to identify the influence of profitability, liquidity, and dividend policy towards firm value in consumer goods companies listed in Indonesia Stock Exchange (IDX) for the period of 2018 to 2020. In this paper, the writer is using purposive sampling method to select the sample of the research. As a result, there are 21 consumer goods companies which are chosen as research sample because they fulfilled the sample criteria for this research, therefore there are 63 samples in total for the period of three years. The data of the research is processed through SPSS 25. Based on data analysis result, it can be concluded that profitability has significant influence on firm value. On the other hand, liquidity and dividend policy do not give significant influence on firm value. Profitability, liquidity, and dividend policy simultaneously give significant influence on firm value.